E-Kiosk : Digitizing the Sonobudoyo Museum Collections - Daru Prasetyawan; Agus Mulyanto (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2018)
E-kiosk is one of the medias in culture and tourism development in Indonesia. E-kiosks can provide information that can add to the curiosity of tourists towards cultural heritage objects, especially museum collections in Indonesia. This research aims to build e-kiosk applications with experimental design method to develop applications that are integrated with the database. The e-kiosk application was developed in collaboration with Flash programs, ActionScript, PHP, XML, and Microsoft Accsess so as to produce a multimedia application that is integrated with the database.